Targeted nonviral gene therapy in prostate cancer - Altwaijry, Najla (Int J Nanomedicine, 2018)
Prostate cancer is the second-most widespread cancer in men worldwide. Treatment choices are limited to prostatectomy, hormonal therapy, and radiotherapy, which commonly have deleterious side effects and vary in their efficacy, depending on the stage of the disease. Among novel experimental strategies, gene therapy holds great promise for the treatment of prostate cancer. However, its use is currently limited by the lack of delivery systems able to selectively deliver the therapeutic genes to the tumors after intravenous administration without major drawbacks. To remediate this problem, a wide range of nonviral delivery approaches have been developed to specifically deliver DNA-based therapeutic agents to their site of action. This review provides an overview of the various nonviral delivery strategies and gene therapy concepts used to deliver therapeutic DNA to prostate cancer cells, and focuses on recent therapeutic advances made so far.